Motivations for concurrent use of uppers and downers among people who access harm reduction services in British Columbia, Canada: findings from the 2019 Harm Reduction Client Survey. Issue 5 (2nd May 2022) - Steinberg, Abigail; Mehta, Amiti; Papamihali, Kristi; Lukac, Christine D; Young, Sara; Graham, Brittany; Lock, Kurt; Fleury, Mathew; Buxton, Jane A
Abstract : Introduction: An increase in crystal methamphetamine (methamphetamine) use during the overdose epidemic is being observed in British Columbia (BC), Canada, and across North America. Concurrent use (ie, using uppers and downers one after the other or together) can increase the risk of fatal and non-fatal opioid overdose. Objectives: We investigated motivations for concurrent use of uppers and downers, specifically how (eg, in what order) and why people use concurrently, to identify potential interventions to prevent overdose and other harms. Setting and participants: The 2019 Harm Reduction Client Survey was administered across 22 harm reduction supply distribution sites in BC (n=621). This thematic analysis examined 307 responses by people who affirmed concurrent use to classify order and reasons for using uppers and downers concurrently. Results: Of the 307 people who responded 'yes' to concurrent use, 179 (58.3%) used downers then uppers, 76 (24.8%) used uppers then downers and 184 (59.9%) mixed uppers and downers together. Four main reasons for concurrent use emerged: self-medication, availability and preference, drug effects/properties, and financial and life situation. People who mixed drugs together predominantly wanted to achieve desired drug effects/properties, such as a specific high or balancing stimulating and sedating effects. Conclusions: The ongoing rise in overdoses in BC is multifactorial, and the recent parallel increases in methamphetamine use and concurrent use with opioids may contribute. Qualitative interviews may further elucidate reasons for concurrent use. Addressing reasons for concurrent use identified in this study through harm reduction strategies and education may affect the rates of overdose morbidity and mortality.